(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study highlights the importance of marketing for the sustainability and advancement of companies in the current era. Content marketing, product innovation, and online customer ratings are identified as key factors influencing purchasing decisions. The quantitative method used in this study, conducted at Kencana Collection Bali, involving 100 respondents. The results indicate that content marketing, product innovation, and online customer ratings significantly and positively affect purchasing decisions. Simultaneously, these three factors collectively contribute to a 56.8% influence on purchasing decisions. Recommendations for Kencana Collection Bali’s management include enhancing competitiveness against other online shopping sites, carefully selecting influencers to build consumer trust, improving product innovation in terms of style and design to remain competitive, and delivering credible information to consumers. These suggestions are expected to enhance the company’s market position and strengthen customer relationships.